Facilitating effects of plant extracts on soil health and replanted Panax ginseng growth in recession soil - Wang, Ergang; Zhou, Yi; Miao, Xinyue; He, Guixiang; Lv, Pengyuan; Wang, Lixiang; Zhan, Yu; Chen, Changbao; Li, Qiong (PLOS ONE, 2024)
Background Plant extracts have been shown to be effective agricultural strategies for improving soil fertility and quality, and promoting plant growth in soil degradation remediation. The application of plant extracts improves the material cycle of soil microecology, such as the decomposition of nitrogen, phosphorus, and potassium, while increasing plant resistance. However, there is currently no experiment to demonstrate whether plant extracts have a promoting effect on the growth of ginseng and the mechanism of action. Objectives and methods Pot experiments were carried out to investigate the effects of extracts, namely Rubia cordifolia (RC), Schisandra chinensis (SC), and Euphorbia humifusa (EH) on soil properties, enzyme activities, and plant physiological characteristics were evaluated. Results Results showed that compared with CK, plant extract-related treatments increased soil Organic carbon (OC), Available nitrogen (AN), Available phosphorus (AP) contents, and Soil urease activity. (S-UE), Soil sucrase activity (Soil sucrase), Soil acid phosphatase activity. (S-ACP). Meanwhile, plant extract-related treatments significantly increased plant physiological properties and TP (Total protein) content, and decreased the content of MDA (malondialdehyde) by 15.70% -36.59% and PRO (proline) by 30.13% -148.44%. Furthermore, plant extract-related treatments also significantly promote plant growth and reduce plant incidence, the fresh weight of ginseng increased by 27.80% -52.08%, ginseng root activity increased by 45.13% -90.07%, and ginseng incidence rate decreased by 20.00% -46.67%. Through correlation analysis between fresh weight of ginseng and root parameters and soil index, fresh weight is significantly positively correlated with root diameter, fiber root number, root activity, total protein (TP), catalytic activity (CAT) and superoxide dismutase activity (SOD), H, soil urea activity (S-UE), soil sucrose activity (S-SC), soil acid phosphate activity (S-ACP), and soil laccase activity (SL); The fresh weight was significantly negatively correlated with incidence rate, disease severity index, and malondialdehyde content (MDA). Conclusion In summary, plant extract-related treatments improve soil quality and promote ginseng growth, further enhancing soil health and plant disease resistance. These findings provide new insights into ginseng cultivation and soil health management and highlight a new approach that can be applied to a wider range of agricultural practices and environmental sustainability.